2015
DOI: 10.1186/s12864-015-1373-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of the salt-stress response in the halophyte Halogeton glomeratus

Abstract: BackgroundHalogeton glomeratus (H. glomeratus) is an extreme halophyte that is widely distributed in arid regions, including foothills, the Gobi desert of northwest China, and the marginal loess of Central Asia. However, research on the salt-tolerant mechanisms and genes of this species are limited because of a lack of genomic sequences. In the present study, the transcriptome of H. glomeratus was analyzed using next-generation sequencing technology to identify genes involved in salt tolerance and better under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 57 publications
10
42
1
Order By: Relevance
“…Consistent with our results, previous studies have shown that the levels of proteins related to CO 2 assimilation and light reactions of the Calvin cycle increased under salt stress (Wang et al. ). In addition, many studies have reported that the photosynthetic activity of algae under moderate stress is still high (Gao et al.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results, previous studies have shown that the levels of proteins related to CO 2 assimilation and light reactions of the Calvin cycle increased under salt stress (Wang et al. ). In addition, many studies have reported that the photosynthetic activity of algae under moderate stress is still high (Gao et al.…”
Section: Discussionsupporting
confidence: 93%
“…TF BTF3 homolog 4‐like was down‐regulated at 72 hr dehydration. BTF3 was earlier reported in salt stress response (Wang et al, ). Transcription repressor OFP1, transcription initiation factor IIE subunit alpha‐like and probable NOT transcription complex subunit VIP2 isoform X1 showed consistent up‐regulation under dehydration.…”
Section: Resultsmentioning
confidence: 76%
“…The effect of salinity on decomposition may be attributed to low microbial activity 8 . High salinity severely affects plant growth 21 and productivity 22 , though some plants have physiological mechanisms to tolerate and recover from high salt stress 23 . On the other hand, the ameliorative role of SOD against oxidative stress is well documented 24,25 .…”
Section: Discussionmentioning
confidence: 99%